Pemanfaatan Media Visual untuk Meningkatkan Pemahaman Pembelajaran Ekonomi dalam Kurikulum Merdeka Berbasis Deep Learning di SMA Negeri 1 Surakarta - Salma Salsabila; Victonia Anggraini (Jurnal Kajian dan Penelitian Umum, 2025)
This study aimed to examine the use of visual learning media in economics lessons, based on the deep learning-based Independent Curriculum at SMA Negeri 1 Surakarta. This study employed a qualitative approach with a descriptive design. The informants included economics teachers and grade X.11 students at SMA Negeri 1 Surakarta. Data collection involved interviews, direct observation, and documentation. The results indicated that the use of visual learning media in economics lessons has not been optimally implemented and is still dominated by conventional learning media, such as whiteboards accompanied by verbal explanations. This situation reflects a discrepancy between classroom learning and the demands of the Independent Curriculum, which prioritizes meaningful learning through deep learning. To address this issue, students in the Introduction to School Environment (PLP) program implemented visual learning media, one of which was a smart box, to create a more engaging, interactive, and enjoyable learning process. The application of this visual learning media has been shown to improve students' understanding of economic activities and encourage student activeness in the question-and-answer process, resulting in more meaningful learning in accordance with the principles of the deep learning-based Independent Curriculum.